RELASI GENDER DALAM KAJIAN ISLAM “THE TAO OF ISLAM, KARYA SACHIKO MURATA” - Atika Zuhrotus Sufiyana (Tadrib: Jurnal Pendidikan Agama Islam, 2017)
Listened more closely, Sachiko's cosmological and theological approach of murata flourished from the view of men and women, the word of Allah: "and everything we created in pairs". Couples who are often called dalm al-Qur'an that can be interpreted as a picture of the cosmos is the sky and earth. A number of verses imply that everything in the universe is covered by both of these. In this discussion, we can find the special feature of Sachiko Murata's thinking lies in the approach that uses cosmological and theological approach, followed by Chinese cosmology which focuses on the thinking of Chinese and Islamic philosophy which depicts the universe within the boundaries of Yin and Yang principles. In an easily digestible language, Sachiko murata attempts to analyze gender relations through cosmological theory in Islam, by emphasizing the concept of Tajalliyat Ibn 'Arabi, which is similar to Emotion's emancipation theory. In the Qur'an, there are 99 names of Allah that show these two attributes. He concludes that the Feminine Masculine mapping of gender differences of identity when associated with God as a source of human and natural existence, then every human being has masculine and feminism, as the phenomenon of day and night, darkness, and so on.The product of his thinking about gender relations became clearer, when Sachiko murdered the argument in the form of an analogy of the creation of the heavens and the earth (male and female relationships such as the relationship of heaven and earth), the degree of men to women and in marriage, all of which came from reality cosmology. A woman in relation to a man is like Nature in relation to divine command, because woman is the locus for the existence of children. Nature in relation to the divine command is the locus of the embodiment for the entities of the physical bodies. Through the laws of nature they are born and from themselves they become manifest. There is no command without the laws of nature and there is no law of nature without command. Understanding the degree of men over women, men are superior to one level above women in terms of cosmological justification, not merely based on the text of the Qur'an. While the woman's degree is elevated when the position of women as the recipient of the activity of men, means women have the advantage over the uterus as a manifestation of the survival of natural reproduction and women are made alluring so that men give love, affection to women because women are part of men. Here is where God makes men and women equal in the case of Shari'a.